Optimal Capacitor Placement in Radial Distribution Networks - Sharma, Sarika (My University, 2020)
Electricity generated from the power stations can be distributed to the customers utilizing various systems and amongst these networks the radial distribution network is an alluring one. Power loss happened in this system can be endured and the voltage profile can be enhanced by putting optimal sized capacitors at the appropriate locations. Different calculations and methods are utilized beforehand for investigating the situation where the capacitors to be placed and its sizes. A methodology is proposed that decides the exact sensitive nodes of the radial distribution networks for integrating optimal capacitor placement to reduce power loss, energy loss and to upgrade the voltage profile by means of Loss Sensitivity Factor (LSF) technique and Hybrid ABC-PSO algorithm. The LSF method is applied to find the sensitive nodes and the optimal size of the capacitor has been solved by Hybrid ABC-PSO algorithm. Capacitor placement issue is remarkably a nonlinear problem and from the Fuzzy Inference System (FIS) the most appropriate nodes for the capacitor placement has been picked up. The capacitor size identifying with minimum real power loss has been settled. The proposed procedure is tested on 69-node and 34-node radial distribution networks and the outcomes in both cases are contrasted with other existing methods. A fuzzy expert system (FES) comprising a game-plan of heuristic principles is then utilized for getting the capacitor position suitability of every node in the flow structure. The sizing of capacitor is determined by utilizing Hybrid Artificial Bee Colony-Cuckoo Search Optimization (ABC-CSO) algorithm. The proposed capacitor allocation is executed on 69-node and 34-node radial distribution networks and the outcome is assessed. Recreation outcomes have demonstrated that the proposed technique has decreased the overall losses of the system compared with the existing approaches and also by the ABC-PSO algorithm. The expansion of a 33-node radial distribution network through particle swarm optimization (PSO) is carried out by considering the objectives like power loss, short circuit capacity as well as energy not supplied function. Then from the obtained modified or expanded distribution network, optimal positions of the capacitors have been carried out by using hybrid ABC-CSO algorithm by considering different loading conditions. Initially expansion of planning of distribution system is done before carrying out planning of capacitor. Under these different loading conditions, the required capacitive reactive power is computed for decreasing power losses and enlightening the voltage profile. Then finally, the impact of load progress in the distribution system is analysed before and after capacitor placement. Investigational outcomes specified the efficiency of the projected technique for expansion of distribution and capacitor placement shows high performance and the best method for planning of efficient distribution system.
Ph.D. Thesis
Keywords: Optimal; Radial; Distribution; Networks; ABC-PSO; ABC-CSO